2017
DOI: 10.1177/1533034617735454
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Related Geometric Distortions in Stereotactic Radiotherapy Treatment Planning: Evaluation and Dosimetric Impact

Abstract: In view of their superior soft tissue contrast compared to computed tomography, magnetic resonance images are commonly involved in stereotactic radiosurgery/radiotherapy applications for target delineation purposes. It is known, however, that magnetic resonance images are geometrically distorted, thus deteriorating dose delivery accuracy. The present work focuses on the assessment of geometric distortion inherent in magnetic resonance images used in stereotactic radiosurgery/radiotherapy treatment planning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 46 publications
3
97
0
1
Order By: Relevance
“…For most radiation therapy applications, an accuracy of 1 mm or higher is necessary . In cases where the target size is smaller, geometric accuracy becomes a more critical issue, for example, for a target size of 3 cm, geometric distortions of 1.5 mm may impact the dose to 95% of the volume . According to a recent consensus paper from seven clinical institutes, in the case of MRI simulation for external beam radiation therapy, geometric distortion of <2 mm in the central region of treatment is deemed to be acceptable for sites such as brain, head and neck, and cervix .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For most radiation therapy applications, an accuracy of 1 mm or higher is necessary . In cases where the target size is smaller, geometric accuracy becomes a more critical issue, for example, for a target size of 3 cm, geometric distortions of 1.5 mm may impact the dose to 95% of the volume . According to a recent consensus paper from seven clinical institutes, in the case of MRI simulation for external beam radiation therapy, geometric distortion of <2 mm in the central region of treatment is deemed to be acceptable for sites such as brain, head and neck, and cervix .…”
Section: Discussionmentioning
confidence: 99%
“…Subject‐specific distortions are mainly due to the chemical shift and magnetic susceptibility while GNL and field inhomogeneity are system‐specific causes of distortion. Several factors such as type and field strength of the MR scanner, imaging sequence, and receiver bandwidth can influence the magnitude of distortions from one or more of these sources . It has been shown that at low magnetic field strengths, effects of susceptibility and chemical shift are negligible .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies evaluated the geometric distortion and dosimetric effect using different approaches. Eleftherios et al . detected up to 2 mm geometric distortion for a range of radial distances up to approximately 135 mm by performing rigid spatial co‐registration between MR and CT images, and investigated the dosimetric uncertainties caused by spatial offsets of 0.5 up to 3 mm to the target locations.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, increased conformity and presence of steep dose gradients in SRS treatment plans demand increased spatial accuracy in order to ensure effective treatment delivery, as spatial errors of just a few millimeters can induce considerable target underdosage, especially in tiny brain lesions. [6][7][8] Volumetric modulated arc therapy (VMAT) is commonly employed for SRS treatment delivery. Several studies have demonstrated that multiarc noncoplanar VMAT can deliver highly conformal plans to the target(s) and spare adjacent critical structures.…”
Section: Introductionmentioning
confidence: 99%